Altered prepulse inhibition of the acoustic startle response in BDNF-deficient mice in a model of early postnatal hypoxia: implications for schizophrenia - Lima Ojeda, Juan Manuel Valentino; Inta, Dragos (European archives of psychiatry and clinical neuroscience, 2019)
The brain-derived neurotrophic factor (BDNF) is a major proliferative agent in the nervous system. Both BDNF-deficiency and perinatal hypoxia represent genetic/environmental risk factors for schizophrenia. Moreover, a decreased BDNF response to birth hypoxia was associated with the disease. BDNF expression is influenced by neuronal activity and environmental conditions such as hypoxia. Thus, it may partake in neuroprotective and reparative mechanisms in acute or chronic neuronal insults. However, the interaction of hypoxia and BDNF is insufficiently understood and the behavioral outcome unknown. Therefore, we conducted a battery of behavioral tests in a classical model of chronic early postnatal mild hypoxia (10% O2), known to significantly impair brain development, in BDNF-deficient mice. We found selective deficits in measures associated with sensorimotor gating, namely enhanced acoustic startle response (ASR) and reduced prepulse inhibition (PPI) of ASR in BDNF-deficient mice. Unexpectedly, the alterations of sensorimotor gating were caused only by BDNF-deficiency alone, whereas hypoxia failed to evoke severe deficits and even leads to a milder phenotype in BDNF-deficient mice. As deficits in sensorimotor gating are present in schizophrenia and animal models of the disease, our results are of relevance regarding the involvement of BDNF in its pathogenesis. On the other hand, they suggest that the effect of perinatal hypoxia on long-term brain abnormalities is complex, ranging from protective to deleterious actions, and may critically depend on the degree of hypoxia. Therefore, future studies may refine existing hypoxia protocols to better understand neurodevelopmental consequences associated with schizophrenia.
Gesehen am 07.10.2019
Published online: 16 February 2018